Degraded Land Analyses of Brantas River Basin to Support Land Rehabilitation - Nining Wahyuningrum; Pamungkas Buana Putra (Foresty Faculty of Hasanuddin University, 2019)
Land degradation in the Brantas River Basin occurs very massively as reflected by high erosion and sedimentation. Information related to soil erosion is important since it is one of the basic information in determining the degraded land in a watershed. The purpose of this study was to analyze and identify the distribution of degraded land in the Brantas river basin as an effort to mitigate land degradation through forests and land rehabilitation in suitable locations. Erosion analysis was carried out spatially on a watershed scale using the USLE (Universal Soil Lost Equation) method. Analyses showed that weighted soil erosion values in the Brantas river basin were448.73 tons/ha/year which was classified as high erosion level. The area of 408,818 ha (41.74%) of Brantas river basinneeds erosion handling because 22.51% was identified in the high erosion value category and 19.23% was included in very high erosion values. Those areas were identified as protected forests, production forests, dry land, and mixed gardens. The type of soil and the erodible of soilare part of the determinants of the high value of erosion, but these factors are difficult to manage while land cover types and land management which are the causes of erosion are relatively manageable. The approach to rehabilitate forests and land can be used as an effort to prevent and reduce erosion by taking into account the selection of related types of habitus (form and stratification) and economic value.